Integrating Empirical Software Engineering practice in South America - Robiolo, Gabriela (2015)
Empirical software engineering (ESE) is a sub-domain of software engineering which focuses on experiments on software systems. Its main interest lies on devising software experiments, on collecting data from these experiments, and on formulating laws and theories from these data. In South America there is a group of researchers that are involved in this topic and have interests in common. This project propose the integration of their work in order to reply the experimentation done in different countries contributing to the increase of empirical software engineering body of knowledge. At this time several publications have been done with the collaboration of master students.